Perlindungan Hukum Terhadap Konsumen Jasa Titip Online Dalam Hal Terjadinya Cacat Produk - Kadek Bramanta Rudi Kaze; I Nyoman Putu Budiartha; Luh Putu Suryani (Jurnal Preferensi Hukum, 2024)
The development of the online shopping system has given rise to new business opportunities, one of which is known as a buying and selling service. One of the risks for users of ticketing services is the danger of defects in products received by users of online ticketing services. Based on this, what is the legal protection form of consumers of online ticketing services in the event of a defect in the product received? And how are online delivery service business actors responsible for losses received by consumers for defective goods products. This research uses a normative type of legal research. There are two forms of legal protection for consumers of online ticketing services in the event of product defects received through online buying and selling services, namely preventive and repressive legal protection which can be seen in the provisions of the UUPK. The responsibility of online delivery service business actors for losses received by consumers for defective goods products, in addition to rights and obligations, there are also responsibilities that must be carried. This responsibility is part of a binding obligation in the activities of running a business.